A New Tiapride Selective Electrode and Its Clinical Application - Ortuño, Joaquín A. (Molecular Diversity Preservation International (MDPI), 2007)
The construction and electrochemical response characteristics of a poly(vinyl chloride) (PVC) membrane selective electrode for the determination of tiapride (TPD) are described. The sensing membrane comprised an ion-pair formed between the protonated drug and tetraphenylborate (TPB(-)) in a plasticized PVC matrix. The influence of membrane composition on the electrode response was studied. The electrode showed a fast, stable and Nernstian response over a wide tiapride concentration range (1x10(-5)-1x10(-2) M) with a slope of 57.5±0.2 mV dec(-1) of concentration, a detection limit of 4.3x10(-6)±2.5x10(-7) M, a wide working pH range (2-8) and a fast response time (< 5 s). The electrode showed good selectivity towards tiapride with respect to some inorganic and organic compounds. The electrode has been applied to the determination of tiapride in human urine and iontophoresis solution.